ROLE OF TRANSLATION IN BRIDGING LINGUISTIC AND CULTURAL DIVIDES IN PAKISTAN: A SOCIO-LINGUISTIC ANALYSIS - Saima Jamshaid; Nazia Anwar; Ayaz Z. Noorani (International Journal of Contemporary Issues in Social Sciences, 2024)
The research was primarily conducted to explore how translation binds different linguistic communities together in Pakistan and to figure out the issues and suggestions related to translation to foster effective cross-cultural communication in Pakistan. Purposive sampling was used to recruit 10 teachers (from 10 different languages) who perform translation tasks. The teachers were invited to participate in a focus group discussion with the researcher and were subsequently interviewed by the researcher using a semi-structured interview guide. The findings reveal the convoluted picture of translation in Pakistan and serve as a wake-up call for establishing an institutionalized framework of inter-linguistic communication that allows communities to engage effectively. In the study, one approach recommended to deepen intercultural understanding and develop this competence is translation, as a way of bridging what amounts to a whispered canyon between languages across Pakistan. The study further highlights an urgent need to create and roll out standard translation resources and controls to normalize the translation and, in turn, enable reliable and comparable translation data across diverse linguistic contexts.